Frequency and Patterns of Brain Infarction in Patients With Embolic Stroke of Undetermined Source: NAVIGATE ESUS Trial. Issue 1 (20th September 2021) - Sharma, Mukul; Smith, Eric E.; Pearce, Lesly A.; Shoamanesh, Ashkan; Perera, Kanjana S.; Coutts, Shelagh B.; Damgaard, Dorte; Ameriso, Sebastian F.; Rha, Joung-Ho; Modrau, Boris; Yoon, Byung-Woo; Romano, Marina; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The spectrum of brain infarction in patients with embolic stroke of undetermined source (ESUS) has not been well characterized. Our objective was to define the frequency and pattern of brain infarcts detected by magnetic resonance imaging (MRI) among patients with recent ESUS participating in a clinical trial. Methods: In the NAVIGATE ESUS trial (New Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial Versus ASA to Prevent Embolism in Embolic Stroke of Undetermined Source), an MRI substudy was carried out at 87 sites in 15 countries. Participants underwent an MRI using a specified protocol near randomization. Images were interpreted centrally by those unaware of clinical characteristics. Results: Among the 918 substudy cohort participants, the mean age was 67 years and 60% were men with a median (interquartile range) of 64 (26–115) days between the qualifying ischemic stroke and MRI. On MRI, 855 (93%) had recent or chronic brain infarcts that were multiple in 646 (70%) and involved multiple arterial territories in 62% (401/646). Multiple brain infarcts were present in 68% (510/755) of those without a history of stroke or transient ischemic attack before the qualifying ESUS. Prior stroke/transient ischemic attack ( P <0.001), modified Rankin Scale score >0 ( P <0.001), and current tobacco use ( P =0.01) were associated with multiple infarcts. Topographically, large and/or cortical infarcts were present in 89% (757/855) of patients with infarcts, while in 11% (98/855) infarcts were exclusively small and subcortical. Among those with multiple large and/or cortical infarcts, 57% (251/437) had one or more involving a different vascular territory from the qualifying ESUS. Conclusions: Most patients with ESUS, including those without prior clinical stroke or transient ischemic attack, had multiple large and/or cortical brain infarcts detected by MRI, reflecting a substantial burden of clinical stroke and covert brain infarction. Infarcts most frequently involved multiple vascular territories. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02313909.